p145, a protein with associated tyrosine kinase activity in a human gastric carcinoma cell line. - Giordano, S (1988)
A protein with an Mr of 145,000 (p145) was detected by antibodies to phosphotyrosine by Western blot (immunoblot) analysis. This protein was phosphorylated on tyrosine in a gastric carcinoma cell line. In cells that were metabolically labeled with 32Pi, this protein was phosphorylated on tyrosine and serine. p145 is a cysteine-rich transmembrane glycoprotein. The extracellular domain could be labeled by 125I under nonpermeating conditions and was cleaved by mild trypsin treatment of intact cells. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis under nonreducing conditions revealed a shift of p145 mobility to an apparent Mr of 190,000. After immunoprecipitation with phosphotyrosine antibodies, p145 displayed a strong associated protein kinase activity in vitro, becoming phosphorylated on tyrosine. There was no immunological cross-reaction between p145 and known tyrosine kinases. Both in vivo and in vitro tyrosine phosphorylations were unaffected by the addition of known growth factors. However, p145 was rapidly dephosphorylated in vivo when cells were exposed to low pH, a condition that is known to dissociate ligands from their receptors. These data suggest that p145 is associated with a protein tyrosine kinase activity which, in the tumor cell line studied, is activated by an as yet unidentified factor.